The Effect of Servant Leadership on Establishment of Organizational Citizenship Behavior (OCB) Through Organizational Commitment of Employee in PT. Awam Bersaudara - Awwab Hafidz Al Faruqi* (Airlangga Development Journal, 2019)
Organizational Citizenship Behavior (OCB) is seen as an alternative strategy for companies in managing human resource behavior, including family businesses that have their own characteristics. The family company is currently actively making changes as the implication of the dynamic business world and intense competition. Therefore we need Organizational Citizenship Behavior (OCB) applied by the employees to improve work productivity and maintain the company's existence. The leadership characteristics or servant leadership and organizational commitment are external factors in the formation of employee’s Organizational Citizenship Behavior (OCB). This research was conducted to test, analyze and determine the effect of servant leadership on the formation of Organizational Citizenship Behavior (OCB) through organizational commitment to employees in PT. Awam Bersaudara. This study uses a quantitative approach with 139 respondents who are employees of PT. Awan Bersaudara. The results of this study indicate that there is a direct influence between servant leadership on Organizational Citizenship Behavior (OCB) with a significance value of 0.666 (<0.5) and there is an indirect effect between servant leadership on Organizational Citizenship Behavior (OCB) through organizational commitment as a moderator variable indicated by the value of 0.013 (<0.5), which proved that organizational commitment as moderator variable strenghten the relation of servant leadership towards Organizational Citizenship Behavior (OCB).